Piecing It All Together - Gould, Leslie 1962- (Thorndike, Maine : Center Point Large Print, 2021)
"After Savannah Masts fianc♭? dumps her a week before their wedding, she flees California for the safety of her Amish grandmothers farm near Nappanee, Indiana, where she used to spend her summers. Savannah intends her stay to be brief, but when an Amish woman goes into labor in the middle of a blizzard and needs Savannahs help, she finds herself unexpectedly entangled in their familys drama. The womans oldest daughter, Miriam, goes missing and Savannahs childhood friend Tommy Miller is implicated. Jane Berger, the local historian and owner of a nearby quilt shop, tells a similar tale of another womans disappearance in the 1800s, inspiring Savannah to do all she can to help with the search for Miriam. But when Tommys own cousin testifies against him, she isnt sure who she can trust. And when events stir up painful memories of her mother, she must face her own truth: that her engagement isnt the only thing in her life that is broken."--
Keywords: Amish -- Fiction; Missing children -- Fiction; Nappanee (Ind.) -- Fiction; Christian fiction; Detective and mystery fiction; Fiction; Christian fiction; Mystery fiction; Christian fiction; Detective and mystery fiction